INVESTIGATIONS OF TIME AND ECONOMIC DIMENSIONS OF THE COMPLEX PRODUCT PRODUCTION CYCLE - Jovanović, Jelena R; Milanović, Dragan D; Radović, Milić; Đukić, Radisav D (Journal of Applied Engineering Science, 2012)
The features of contemporary production process of top organization and management methods are grounded on the principles of economies of times and the principles of lean production, a new philosophy of production. Production should be organized according to the push-pull principle, with minimum inventories, manufacturing only what is really necessary, neither too early, nor too late. The paper presents the design procedure and results of investigations on the production cycle of a complex product included in the production program of “Sloboda” – Cacak Co. Key words: complex product, production cycle, design, coefficient of running time, current assets